Reformas neoliberais e política de formação continuada de professores nos Governos do Novo Pará (1995-2006) - AQUINO, Edward Martins de (Universidade Federal do Pará, 2011)
This work talks about the teachers formation, thought the often modality what is for the teachers of basic education, in high school, in the state of Pará, determined by the governmental politic, while the period with the name New Pará (1996-2006). Interrogating the configuration that assumed the politic of frequent formation executed by the governments of Pará, and the presuppositions that oriented the formulation of your formations politic, your objective is understand all kinds of often formulation of teachers in Brazil, converging for your specificities in Pará in face of took measures by your governments, in the historic period of 1995-2006, knowing the characteristics assumed by often formation politic for the teachers of Basic Education of Pará, like your defects in teaching activity. Your methodic option, localized in the bibliographic research and documental analyze, thought the access to the official documental sources and in a focalized literature in the thematic in question, in the circuit of governmental politic education of that time. What is interesting is your relation with the scenery what is behind of everything, specially, the Brazilian states reform, during the 90s, with the influence of new liberal ideologies, with reflexes in education. With your conclusion, it was possible to infer by presence of this modality of formation, than the Specialization Lato Sensu History of Amazon, realized by the Amazons University UNAMA, in the period 2003/2004, is illustrative, but in the fragmental and indicial form, characterizing a inconsistent politic, fragile and tenuous, across of a fast process, created in a rational and instrumental boarding, with distinction in the reference of Competences Pedagogies. But, separated of a project more articulated in a high school universe, seeing in a way critical for the educational practice, putting that the education is a permanent territory of fight of projects and interests.